[PP.32.04] PREDICTORS OF PWV PROGRESSION OVER A THREE YEARS FOLLOW UP: FOCUS ON PSYCHOLOGICAL CHARACTERISTICS. (September 2016) - Sormani, P.; Colombo, G.; Greco, A.; Maloberti, A.; Franzosi, C.; Meani, P.; Varrenti, M.; Vallerio, P.; De Chiara, B.; Casadei, F.; Moreo, A.; D'Addario, M.; et al.
Abstract : Objective: Abnormal large artery function plays an important role in the pathogenesis of cardiovascular (CV) diseases. Prior studies have suggested that the principal determinants of arterial stiffening are age, Blood Pressure (BP) and others CV risk factors such as dyslipidemia and diabetes. However the role of psychological characteristics on the long-term progression of arterial stiffness has not yet been evaluated. The aim of the current longitudinal study was to evaluate the psychological determinants of the Pulse Wave Velocity (PWV) progression over a 3 years follow-up period in treated hypertensives subjects. Design and method: We enrolled 350 consecutive 18–80 aged outpatients, followed by the Hypertension Unit of S. Gerardo Hospital (Monza, Italy) affected by essential hypertension. At baseline (T0) anamnestic data, clinical BP, laboratory data and PWV were evaluated; also psychological tests were performed. In a subgroup of 50 subjects, after a median follow-up time of 2.96 ± 0.33 years, we performed again psychological tests and PWV examination (T1). Psychological tests were administered by trained researchers for measuring perceived stress, resiliency factors (self-esteem, sense of coherence), and perceived social support. Results: At T0 the mean age was 55.9 ± 10.1years, SBP and DBP were 135.6 ± 17.7 and 82.5 ± 9.1mmHg and PWV was 8.6 ± 2.1m/s. Despite a significant improvement in the blood pressure control (from 72 to 84%; PAS from 135.6 ± 17.7 to 130.1 ± 14.2, p = 0.08; PAD from 82.5 ± 9.1 to 77.5 ± 9.4, p < 0.05), at follow-up examination PWV didn't showed significant changes (from 8.6 ± 2.1 to 8.6 ± 2.4, p = 0.87) with a mean deltaPWV of −0.05 ± 2.8m/s. Focusing on PWV changes over the follow-up period and on psychological test, subjects where then divided accordingly to their deltaPWV in those in which an increase was showed and those in which the values decrease. For similar baseline values, subjects with positive deltaPWV showed higher T1 values of stress (37.4 ± 1.1vs36.8 ± 0.8, p = 0.02) and lower values of self-esteem (2.9 ± 0.5 vs 3.3 ± 0.4, p = 0.02), sense of coherence (4.4 ± 0.7vs4.9 ± 0.8, p = 0.02), and a worse family climate (3.5 ± 0.9vs4.1 ± 0.8, p = 0.02). No significant differences were showed regarding BP values and CV risk factors. Conclusions: The current longitudinal study shows that arterial stiffness didn't shown any significant changes despite BP improvement. PWV increase is related to higher stress and lower self-esteem and familiar support.